The factors influencing securitization performance in Malaysia - Dabas, Nurayati; Bakri, Mohammed Hariri; Mohamad Sharif, Sabri; Ismail, Shafinar (American Scientific Publishers, 2017)
Asset Backed Securitization in Malaysia started in 1986 and many companies have been reported to participated to get benefit of securitization and to improve performance of companies. However, in the end of 2007, United States (U.S) faces on subprime mortgage crisis and affect several countries. This situation effect Malaysia until the end 2008 where Asset Backed Securities stalled and then began to fall because of investors have become more cautious to do any investment and it also affects Securitization Companies. The factor that impacts on securitization companies’ performance in Malaysia is vague. Based on a review of literature, this paper were purposes a model to test the factors that can give an impact on securitization company performance in Malaysia. As indicators of company performance, the Profit after tax and zakat has been used and Liquidity, Leverage, Assets, and Inflation have been use as independent variables. Using a sample of 365 securities issuer from 2004–2012. In the empirical analysis using Statistical Package for the Social Science (SPSS) and the regression methods have been used. Besides that, the results indicate the independent variable have significant relationship on performance of securitization companies in Malaysia.